1998
DOI: 10.1017/s0260305500014579
|View full text |Cite
|
Sign up to set email alerts
|

Irreducible water saturation in snow: experimental results in a cold laboratory

Abstract: The porosity of wet snow is often about 50%; however, liquid water generally fills less than 10% of this pore volume. In order to relate the irreducible water content trapped in snow to its characteristics, we have conducted experiments in a cold laboratory. The results show that irreducible water content, expressed as per cent of mass, depends only on porosity. Experimental studies were restricted to homogeneous wet snow samples. Therefore, we can only achieve a valid result in natural snowpacks when applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 6 publications
(1 reference statement)
3
65
1
3
Order By: Relevance
“…Colbeck (1974) found a value of 0.07 experimentally and Yamaguchi et al (2010) found a value of 0.02, both for snow with a density of about 550 kg m −3 . Coleou and Lesaffre (1998) experimented with variable densities and found an approximate relationship between porosity, P = 1−ρ s /ρ i , and the water per snow-pluswater mass irreducible liquid water content, W mi :…”
Section: Water Saturationmentioning
confidence: 99%
“…Colbeck (1974) found a value of 0.07 experimentally and Yamaguchi et al (2010) found a value of 0.02, both for snow with a density of about 550 kg m −3 . Coleou and Lesaffre (1998) experimented with variable densities and found an approximate relationship between porosity, P = 1−ρ s /ρ i , and the water per snow-pluswater mass irreducible liquid water content, W mi :…”
Section: Water Saturationmentioning
confidence: 99%
“…The original version of SNOWPACK considers a bucket-type approach to simulate water percolation in snow. Accordingly, water is retained at a given position in the profile until it exceeds a threshold (see Coleou and Lesaffre, 1998). After exceeding, excess water is transmitted downwards.…”
Section: The Comparison With Snowpackmentioning
confidence: 99%
“…In the previous RACMO2 snow albedo scheme, the maximum amount of liquid water in the snowpack was limited to 2 %. In the new snow albedo scheme, this artificial limit is no longer applied, and the amount of liquid water in the snowpack is calculated following Coléou and Lesaffre (1998). In their expression, the maximum amount of liquid water is related to the available pore space in the snowpack and can reach values of up to 13 % of the weight of the snowpack (experiment LWMAX).…”
Section: Model Experimentsmentioning
confidence: 99%